Measuring the climate security nexus: The Integrated Climate Security Framework - Pacillo, Grazia; Medina, Leonardo; Liebig, Theresa; Carneiro, Bia; Schapendonk, Frans; Craparo, Alessandro; Ramirez-Villegas, Julian; Basel, Ashleigh; Minoarivelo, Henintsoa Onivola; Achicanoy Estrella, Harold; Villa, Victor; Belli, Anna; et al. (2024)
International, regional, and national organizations, alongside policymakers, are increasingly acknowledging the crucial connection between climate, peace, and security. However, there remains a notable gap in research methodologies capable of fully grasping the intricate dynamics of this relationship. This paper introduces the Integrated Climate Security Framework (ICSF), a comprehensive mixed-methods approach designed to unravel the complexities of climate-human security-conflict connections across various scales. By integrating traditional and innovative research methods, the ICSF aims to provide cutting-edge, policy-relevant insights to address five main measurement challenges of the climate security nexus: multiple pathways; context specificity; non-linearity; multiple actors and scales, and multiple geographic and time scales. By drawing on diverse epistemological perspectives and engaging directly with local communities, the framework offers a comprehensive evaluation of the complex social-ecological dynamics at play. Using Kenya as a case study—a country where climate and security risks frequently intersect and amplify each other—we demonstrate the comprehensive insights the framework offers to address the complex challenges at the nexus of climate, human security, and conflict.